2012
DOI: 10.1029/2012gl052166
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of the organic molecules in the shallow subsurface of Mars due to irradiation by cosmic rays

Abstract: [1] Detection of the organic matter on Mars is one of the main goals of the future Martian landing missions. Yet, the degradation of organic molecules by cosmic ray irradiation on Mars is often ignored. We calculate the radiation dose accumulation rates from solar and galactic cosmic rays at various depths in the shallow Martian subsurface. We demonstrate that a 1-billion-year outcrop on Mars accumulates the dosage of $500 MGy in the top 0-2 cm and $50 MGy at 5-10 cm depths. We show that the preservation of an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
167
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 174 publications
(167 citation statements)
references
References 25 publications
(66 reference statements)
0
167
0
Order By: Relevance
“…Moreover, on Mars, galactic cosmic rays and solar cosmic rays play an important role in the degradation of organic molecules near the planetary surface. Owing to the dosage of the cosmic irradiation, the models by Pavlov et al [88] suggested that organic molecules with masses greater than 100 amu would be effectively destroyed in less than one billion years in the top 5 cm of the Martian rocks. In addition, cosmic rays may produce oxidative radicals which may further increase the rate of degradation of organic molecules.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, on Mars, galactic cosmic rays and solar cosmic rays play an important role in the degradation of organic molecules near the planetary surface. Owing to the dosage of the cosmic irradiation, the models by Pavlov et al [88] suggested that organic molecules with masses greater than 100 amu would be effectively destroyed in less than one billion years in the top 5 cm of the Martian rocks. In addition, cosmic rays may produce oxidative radicals which may further increase the rate of degradation of organic molecules.…”
Section: Discussionmentioning
confidence: 99%
“…Thus we present here extrapolations of the RAD surface dose measurements (using transport models) to the Martian subsurface, with implications for estimating lethal depths and microbial survival times (26)(27)(28)(29)(30). The radiation environment on Mars may also play a key role in the chemical alteration of the regolith and Martian rocks over geologic time scales, affecting the preservation of organics including potential organic biosignatures of the ancient Martian environment (26)(27).…”
Section: Main Text: Introductionmentioning
confidence: 99%
“…Rocks containing the signatures of microbial life will have been exposed at the surface of the planet to radiation for variable lengths of time, depending upon how long they have been uncovered by erosion. While UV radiation only penetrates a few mm into the surface of a rock, cosmic and galactic radiations go much deeper (Pavlov et al 2012).…”
Section: Organic Molecules and Biosignatures At Mars Surfacementioning
confidence: 99%